Inhibitory Properties of Aldehydes and Related Compounds against Phytophthora infestans—Identification of a New Lead - John J. Mackrill; Roberta A. Kehoe; Limian Zheng; Mary L. McKee; Elaine C. O’Sullivan; Barbara M. Doyle Prestwich; Florence O. McCarthy (Pathogens, 2020)
The pathogen Phytophthora infestans is responsible for catastrophic crop damage on a global scale which totals billions of euros annually. The discovery of new inhibitors of this organism is of paramount agricultural importance and of critical relevance to food security. Current strategies for crop treatment are inadequate with the emergence of resistant strains and problematic toxicity. Natural products such as cinnamaldehyde have been reported to have fungicidal properties and are the seed for many new discovery research programmes. We report a probe of the cinnamaldehyde framework to investigate the aldehyde subunit and its role in a subset of aromatic aldehydes in order to identify new lead compounds to act against P. infestans. An ellipticine derivative which incorporates an aldehyde (9-formyl-6-methyl ellipticine, 34) has been identified with exceptional activity versus P. infestans with limited toxicity and potential for use as a fungicide.